Network-based RTK Positioning: Impact of Separating Dispersive and Non-dispersive Components on User-side Processing Strategy - Musa, Tajul A (Springer, 2006)
The concept of network-based positioning has been extensively developed in order to better model the distance-dependent errors of GPS carrier-phase measurements. These errors can be separated into a frequency-dependent or dispersive component (e.g. the ionospheric delay) and a non-dispersive component (e.g. the tropospheric delay and orbit biases). In fact, dispersive and non-dispersive errors have different dynamic effects on the GPS network corrections. The separation of the two is useful for modelling the network corrections and can provide network users with more options for their data processing strategy. A simple running average is proposed in this paper to provide a stable network correction for the non-dispersive term. It is found that the non-dispersive correction can be used to obtain better ionosphere-free measurements, and therefore helpful in resolving the long-range integer ambiguity of the GPS carrier-phase measurements. Once the integer ambiguities have been resolved, dispersive and non-dispersive corrections can be applied to the fixed carrier-phase measurements for positioning step so as to improve the accuracy of the estimated coordinates. Instantaneous positioning, i.e. single-epoch positioning, has been tested for two regional networks: Sydney Network (SYDNET) and Singapore Integrated Multiple Reference Station (SIMRSN), Singapore. The test results have shown that the proposed strategy performs well in generating the network corrections, in fixing ambiguities and in computing a user’s position.